Enhancing the abscopal effect of radiation and immune checkpoint inhibitor therapies with magnetic nanoparticle hyperthermia in a model of metastatic breast cancer. (29th November 2019) - Oei, Arlene L.; Korangath, Preethi; Mulka, Kathleen; Helenius, Mikko; Coulter, Jonathan B.; Stewart, Jacqueline; Velarde, Esteban; Crezee, Johannes; Simons, Brian; Stalpers, Lukas J. A.; Kok, H. Petra; Gabrielson, Kathleen; et al.
Abstract: Purpose: Enhancing immune responses in triple negative breast cancers (TNBCs) remains a challenge. Our study aimed to determine whether magnetic iron oxide nanoparticle (MION) hyperthermia (HT) can enhance abscopal effects with radiotherapy (RT) and immune checkpoint inhibitors (IT) in a metastatic TNBC model. Methods: One week after implanting 4T1-luc cells into the mammary glands of BALB/c mice, tumors were treated with RT (3 × 8 Gy)±local HT, mild (HTM, 43 °C/20 min) or partially ablative (HTAbl, 45 °C/5 min plus 43 °C/15 min), ±IT with anti-PD-1 and anti-CTLA-4 antibodies (both 4 × 10 mg/kg, i.p.). Tumor growth was measured daily. Two weeks after treatment, lungs and livers were harvested for histopathology evaluation of metastases. Results: Compared to untreated controls, all treatment groups demonstrated a decreased tumor volume; however, when compared against surgical resection, only RT + HTM +IT, RT + HTAbl +IT and RT + HTAbl had similar or smaller tumors. These cohorts showed more infiltration of CD3 + T-lymphocytes into the primary tumor. Tumor growth effects were partially reversed with T-cell depletion. Combinations that proved most effective for primary tumors generated modest reductions in numbers of lung metastases. Conversely, numbers of lung metastases showed potential to increase following HT + IT treatment, particularly when compared to RT. Compared to untreated controls, there was no improvement in survival with any treatment. Conclusions: Single-fraction MION HT added to RT + IT improved local tumor control and recruitment of CD3 + T-lymphocytes, with only a modest effect to reduce lung metastases and no improvement in overall survival. HT + IT showed potential to increase metastatic dissemination to lungs. Graphical Abstract: